2002
DOI: 10.1021/bi0119114
|View full text |Cite
|
Sign up to set email alerts
|

8-(Hydroxymethyl)-3,N4-etheno-C, a Potential Carcinogenic Glycidaldehyde Product, Miscodes In Vitro Using Mammalian DNA Polymerases

Abstract: , is a mutagen and animal carcinogen resulting from the reaction of dC with glycidaldehyde. It was synthesized and its phosphoramidite was incorporated site-specifically into a defined 25-mer oligonucleotide. In this study the mutagenic potential of this compound was investigated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 48 publications
4
13
0
Order By: Relevance
“…Compared with pol and pol , the higher activity of pol copying past N 2 ,3-⑀G observed here is similar to that seen previously for other etheno adducts, i.e. 1,N 2 -⑀G (29), 1,N 6 -⑀A (26,49), and 3,N 4 -⑀C (50). With regard to DNA polymerases, the extension pattern is particularly similar to that of bypass of 1,N 2 -⑀G; i.e.…”
Section: Table 2 Summary Of Pol Extension Products From Lc-ms/ms Analsupporting
confidence: 90%
See 1 more Smart Citation
“…Compared with pol and pol , the higher activity of pol copying past N 2 ,3-⑀G observed here is similar to that seen previously for other etheno adducts, i.e. 1,N 2 -⑀G (29), 1,N 6 -⑀A (26,49), and 3,N 4 -⑀C (50). With regard to DNA polymerases, the extension pattern is particularly similar to that of bypass of 1,N 2 -⑀G; i.e.…”
Section: Table 2 Summary Of Pol Extension Products From Lc-ms/ms Analsupporting
confidence: 90%
“…Similarly, pol copied past 1,N 6 -⑀A in the order of preference T Ͼ C Ͼ A Ͼ G (49). The order was G Ͼ A Ͼ C for 1,N 2 -⑀G (29) and A Ϸ G Ͼ C Ϸ T for 3,N 4 -⑀C (50). Pol has the highest misincorporation frequency (although C is preferred 1.5-fold compared with T), which is consistent with the view that pol generally catalyzes errorprone bypass (3).…”
Section: Table 2 Summary Of Pol Extension Products From Lc-ms/ms Analsupporting
confidence: 72%
“…Studies using in vitro replication systems have revealed that the three related Y family enzymes, pols η (Rad30A), ι (Rad30B) and κ (DinB1), are capable of bypassing various DNA lesions [e.g. [28][29][30][31][32][33][34][35][36] that are normally blockers of classical DNA polymerases such as pol α and pol β. However, such translesion syntheses can be error-free or error-prone.…”
Section: 3-bis(2-chloroethyl)-1-nitrosourea (Bcnu) Is An Effective mentioning
confidence: 99%
“…The ability of pol to bypass a number of types of DNA damage has been reported, including guanine modified with N-acetylaminofluorene or BPDE (9 -14), xanthine (15), 8-nitroguanine (16), and guanine modified with oxidized estrogens (17). However, pol has not been judged to be very efficient in bypassing UV photoproducts (9,18), cis-platin-modified DNA (10), 1,N 6 -ethenodeoxyadenine (19), O 6 -MeG (20), or 8-(hydroxymethyl)-3,N 4 -ethenoC (21). Other issues involving pol include up-regulation in lung cancer (22), a possible (but not established) role in somatic hypermutation (23), and a general role in genome maintenance versus instability (24).…”
mentioning
confidence: 99%